Deep brain stimulation for treatment of hemichorea-hemiballism after craniopharyngioma resection: Long-term follow-up - Case report - Capelle, Hans-Holger; Kinfe, Thomas M.; Krauss, Joachim K. (Journal of Neurosurgery, 2011)
Hemichorea-hemiballism is a rare movement disorder that has various causes. In treatment-resistant cases, both thalamic and pallidal functional procedures have been shown to yield beneficial results. Until now it has not been clarified whether the thalamus or the pallidum would yield a superior outcome. After resection of a craniopharyngioma in this patient at the age of 49 years, hemichorea-hemiballism developed, with a latency of several weeks. Because the patient was greatly impaired by the movement disorder, she underwent implantation of deep brain stimulation (DBS) electrodes in the thalamic ventralis intermedius nucleus and the posteroventral lateral globus pallidus internus. Although both pallidal and thalamic stimulation could suppress the movement disorder, the voltage needed was clearly less with thalamic than with pallidal stimulation. At the last available follow-up 25 months postoperatively, complete subsidence of hemichorea-hemiballism was achieved with long-term thalamic stimulation. Long-term DBS therapy is an efficient treatment modality for refractory hemichorea-hemiballism in the long run (> 2 years). A bifocal (thalamic and pallidal) target paradigm allowed selection of the optimal stimulation site. Thalamic DBS was more favorable with regard to energy consumption.
CRIS-Team Scopus Importer:2021-06-23
Keywords: Craniopharyngioma; Deep brain stimulation; Hemichorea-hemiballism; Pallidum; Thalamus